Scalp swelling of long duration - Dahal, P; Rai, S M (Journal of Chitwan Medical College, 2017)
Malignant tumors occurring in the scalp are uncommon. When scalp swellings are asymptomatic, small in size or covered by hair usually they are neglected by patients. This may lead to a potential risk of delay in detection and treatment which may cause poorer results. Here we are presenting the case of scalp swelling of unknown duration and pre-operative investigation had showed benign lesion and was managed accordingly but post operatively it was found malignant and metastasized rapidly and become incurable. So any unusual, ulcerated/pigmented lesion of the scalp we must consider the possibility of a tumor and reconstruction with flap should be done after confirmation of the diagnosis.